Leaf surface structures enable the endemic Namib desert grass Stipagrostis sabulicola to irrigate itself with fog water - Roth-Nebelsick, A. (The Royal Society, 2012)
The Namib grass Stipagrostis sabulicola relies, to a large degree, upon fog for its water supply and is able to guide collected water towards the plant base. This directed irrigation of the plant base allows an efficient and rapid uptake of the fog water by the shallow roots. In this contribution, the mechanisms for this directed water flow are analysed. Stipagrostis sabulicola has a highly irregular surface. Advancing contact angle is 98° ± 5° and the receding angle is 56° ± 9°, with a mean of both values of approximately 77°. The surface is thus not hydrophobic, shows a substantial contact angle hysteresis and therefore, allows the development of pinned drops of a substantial size. The key factor for the water conduction is the presence of grooves within the leaf surface that run parallel to the long axis of the plant. These grooves provide a guided downslide of drops that have exceeded the maximum size for attachment. It also leads to a minimum of inefficient drop scattering around the plant. The combination of these surface traits together with the tall and upright stature of S. sabulicola contributes to a highly efficient natural fog-collecting system that enables this species to thrive in a hyperarid environment.